2010
DOI: 10.1108/13563281011016840
|View full text |Cite
|
Sign up to set email alerts
|

Financial resources and corporate reputation

Abstract: Purpose -The purpose of this paper is to identify convergent elements between corporate reputation and financial resources. The paper seeks to draw parallels between corporate reputation management and corporate financial management in order to define common management principles. Design/methodology/approach -In this paper, the analogy-based approach is used to identify similarities in the functions and risks between corporate reputation and financial resources. This approach is the prerequisite for defining c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 67 publications
0
9
0
1
Order By: Relevance
“…The resource-based view generates a competitive advantage and signals to shareholders and investors who want to make future contracts with the firm (Sweeney, 2009). Prior studies (Brammer and Pavalin, 2006;Sweeney, 2009;Siano et al, 2010) found a positive association between enterprise reputation and financial performance. Therefore, a firm's good reputation enhances share market values, and people trust the firm's information, whereas a lousy reputation reduces the market value of products and services.…”
Section: Enterprise Reputationmentioning
confidence: 92%
“…The resource-based view generates a competitive advantage and signals to shareholders and investors who want to make future contracts with the firm (Sweeney, 2009). Prior studies (Brammer and Pavalin, 2006;Sweeney, 2009;Siano et al, 2010) found a positive association between enterprise reputation and financial performance. Therefore, a firm's good reputation enhances share market values, and people trust the firm's information, whereas a lousy reputation reduces the market value of products and services.…”
Section: Enterprise Reputationmentioning
confidence: 92%
“…Similarly, Shkolnikov et al (2004) declare that corporate reputation is used as a value-creating mechanism. Corroborating, Smith (1994) averred that corporate reputation is commonly drawn as a tool for the development of organisational value. Roberts and Dowling (2002) also say that corporate reputation is used to express a firm's strategic value.…”
Section: Rose and Thomsen (2004) DCmentioning
confidence: 99%
“…In terms of practical implications, Siano, Kitchen and Confetto (2010) suggested that the use of corporate finance management and corporate reputation management (e.g., organisation development management, cooperative management, risk management, crisis management) helps firms develop an appropriate cultural background to assist managers in maintaining corporate reputation. The integration of corporate finance with corporate communication and reputation allows firms to provide better training for managers in a deeper cultural environment, creating advantages for both large and small companies.…”
Section: Managerial Implications: the Uses Of Corporate Reputation Anmentioning
confidence: 99%
“…Bosoa et al (2017), defined financial resources as the utilisation of financial capital that can be changed by the organisations to achieve their goals. On the other hand, Siano, Kitchen, and Confetto (2010) mentioned that financial resources make up the capital, land and labour that signify the element of production.…”
Section: Financial Resources and Integrity Practicementioning
confidence: 99%